SCHEDULING INFORMATION SYSTEM DESIGN AND MONITORING COLLEGE LECTURER IN JAKARTA STMIK - Ristyawati Ristyawati; Eko Hadiyanto., SSi, MM (Jurnal Sistem Informasi, 1997)
Scheduling classes and professors monitoring plays a very important for the continuity lecturesat a university. Scheduling and monitoring STMIK Jakarta not use computer functions optimally,because there are still many weaknesses, among others, information about subjects that havebeen issued are still done manually, so that can happen subjects who had been in out in out again.This thesis tries to provide a solution Scheduling Information System Design and MonitoringLecture Lecturer, hoping to overcome existing weaknesses and the information obtained can bemore quickly and accurately.